2012
DOI: 10.1155/2012/420619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Temperature on the Growth Iron-Filled Carbon Nanotubes as Evidenced by Structural, Micro-Raman, and Thermogravimetric Analyses

Abstract: Tubular structure and well dense of aligned carbon nanotubes (CNTs) were formulated using two-stage catalytic chemical vapor deposition apparatus. In this experiment, aligned CNT was synthesized in the range of 700–900°C temperatures with increment rate of 50°C per sample. The aligned CNT properties were investigated via field emission scanning electron microscope, micro-Raman spectrometer and thermogravimetric analyzer. The experimental results showed that aligned CNT properties were highly dependent on synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…However, we did not observe any significant weight loss for lidocaine at 130°C. Shamsudin et al performed TGA analysis on camphor oil and observed~50% weight loss at~145°C, which is similar to our observations (37). In an accelerated stability study on lidocaine-tetracaine cream, it was seen that lidocaine was more stable than tetracaine (38).…”
Section: Thermogravimetric Analysissupporting
confidence: 87%
“…However, we did not observe any significant weight loss for lidocaine at 130°C. Shamsudin et al performed TGA analysis on camphor oil and observed~50% weight loss at~145°C, which is similar to our observations (37). In an accelerated stability study on lidocaine-tetracaine cream, it was seen that lidocaine was more stable than tetracaine (38).…”
Section: Thermogravimetric Analysissupporting
confidence: 87%
“…The measured ID/IG ratio of 0.77 of the sample grown using the PrL is comparable to samples grown at a much higher temperature of 700 o C without PrL. [30,31] As the effective growth temperature is lower, any slight reduction in material quality represents a good trade off, along with additional benefits of the PrL. Lower structural quality (ID/IG: 1.0 -1.10) of the CNTs is achieved at low temperatures (375 o C) and improved quality (ID/IG: 0.77 -0.93) is achieved at higher temperatures, which is in agreement with previous studies.…”
Section: Growth Of Cnts Using Tin As a Protective Layermentioning
confidence: 65%
“…Lower structural quality (ID/IG: 1.0 -1.10) of the CNTs is achieved at low temperatures (375 o C) and improved quality (ID/IG: 0.77 -0.93) is achieved at higher temperatures, which is in agreement with previous studies. [31,32] The intensity of the 2D peak ( Figure 4a) and hence the I2D/IG ( Figure 4b) ratio increases with increasing the thickness of the TiN based PrL. The 2D peak has been reported to be sensitive to the doping concentration in CNTs.…”
Section: Growth Of Cnts Using Tin As a Protective Layermentioning
confidence: 95%
See 1 more Smart Citation
“…After oxidized silicon flakes were broken by ball milling into smaller pieces to expose the fresh silicon surface, we deposited CNTs and nanoscale carbons by thermal CVD using ferrocene and camphor as precursors. Ferrocene contains iron, which served as both an effective catalyst and a carbon source for the synthesis of CNT [ 39 , 40 , 41 , 42 ]. Camphor is an additional carbon source [ 43 ].…”
Section: Methodsmentioning
confidence: 99%